2019
DOI: 10.1016/j.toxrep.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between aflatoxin-albumin adduct levels and tortilla consumption in Guatemalan adults

Abstract: Highlights AFB 1 a carcinogen found in maize, Guatemala’s main staple, the relationship of maize intake to serum AFB 1 -albumin adducts levels is novel. Among 461 Guatemalan adults found a median maize intake of 344.3 grams per day and a median serum AFB 1 -albumin adduct level was 8.4 pg/mg albumin. A statistically significant association between torti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…3 In addition, our group has found that the most important source of AFB 1 exposure in the population was consumption of tortillas, a primary staple in the Guatemalan diet. 16 This finding was consistent with prior evidence of high AFB 1 levels in maize samples across the country. 17 The current study was designed to assess the association between AFB 1 and cirrhosis in Guatemala.…”
Section: What Are the New Findings?supporting
confidence: 89%
“…3 In addition, our group has found that the most important source of AFB 1 exposure in the population was consumption of tortillas, a primary staple in the Guatemalan diet. 16 This finding was consistent with prior evidence of high AFB 1 levels in maize samples across the country. 17 The current study was designed to assess the association between AFB 1 and cirrhosis in Guatemala.…”
Section: What Are the New Findings?supporting
confidence: 89%
“…The high levels of AFB 1 reported in Guatemala (8,9) are comparable to the levels found in some high-rate parts of China before the transition there from a maize-based to a rice-based diet. (28) In the current study, there were in total 24 mutations with a G->T transversion. The majority of the G->T transversions occurred in codon 249 and the rest were in codons: 157 (n = 2) and 248 (n = 1) (data not shown).…”
Section: Discussionmentioning
confidence: 70%
“…In addition to the main analysis, PORs and 95%CIs were estimated to assess associations between total maize and tortilla consumption with each metabolic condition. 26 All tests of significance were two-sided. P-values less than .05…”
Section: Discussionmentioning
confidence: 99%